Nigerian Development Challenges, Service Delivery, and Fiscal Federalism : An Examination of State and Local Government Roles and Remedial Action - Sulaiman T.H; Abalaka J.N; Ajiteru S.A.R (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2025)
The study looks at fiscal federalism, which is the distribution of resources between federating entities so that they can carry out their constitutional duties. The goal of this study was to identify the fundamental imperatives of fiscal federalism for the advancement of the country. In Nigeria's new democratic environment, the relative roles of the federal government, state governments, and local government authority (LGAs) in providing public services have become one of the most crucial subjects of candid and heated discussion. Federalism, fiscal federalism, and development were conceptually explained from the outset, and it became clear that the principles of fiscal autonomy and integrity are critical to the survival and ongoing existence of a properly federating form of government. In order to ascertain how the federal arrangements affect the provision of basic services in four crucial areas, the analysis will make use of fieldwork conducted in six states and twelve LGAs. primary health care, primary education, clean water and sanitation, and local roads that connect communities to marketplaces, schools, and medical facilities. The paper, which was based on Buchan Fiscal Residuum Theory, attempted to accomplish the study's goal by balancing the value of the public services returned to individuals with the payments paid. According to the article, the conflicting problems and difficulties of fiscal federalism may manifest as a misalignment between the functions of the different levels of government and the sources of money. According to the paper's conclusion and recommendations, it is important to make sure that revenue allocation encourages state and local governments to increase internal revenue generation rather than relying only on funding from In order to clearly define the duties to be carried out by each level of government, the federation account and intergovernmental relations issues should be examined and respected.